High transport Jc in stainless steel/Ag-Sn double sheathed Ba122 tapes. (14th August 2017) - Gao, Zhaoshun; Togano, Kazumasa; Zhang, Yunchao; Matsumoto, Akiyoshi; Kikuchi, Akihiro; Kumakura, Hiroaki
Abstract: In this study, we report that the transport critical current density J c of Ba122 tapes can be significantly enhanced by using the harder stainless steel (SS)/Ag-Sn double sheath. A high J c value of 1.4 × 10 5 A cm −2 (at 4.2 K and 10 T) was achieved in SS/Ag-Sn alloyed double sheathed tapes by cold pressing. Even for as-rolled tapes, the J c exceeds the practical level of 10 5 A cm −2 in magnetic fields up to 10 T. More interestingly, a high J c value of 5.5 × 10 4 A cm −2 at 10 T was obtained by a heat treatment with a very low temperature of 550 °C. The microstructure investigations reveal that the higher core density of the Ba122 tapes with uniform deformation and better grain alignment are responsible for the superior J c -field performance.